The Role of Continuing Education in Environmental Education Management - Windi Megayanti; Robiatul Adawiyah; Nia Sonani (Fakultas Ekonomi Universitas Garut, 2025)
Global environmental issues such as climate change, ecosystem degradation, and increased waste demand sustainable education strategies to foster pro-environmental awareness and attitudes continuously. Continuing education is an important approach to strengthening environmental education management, as it can shape broader public understanding, skills, and participation. This study aims to analyse the influence of continuing education on environmental education management in educational institutions that have implemented sustainability-based programmes. This study uses a quantitative approach with an explanatory design. The research population comprises educators, educational staff, and participants in environmental education programmes. The Lemeshow technique determined the sample, resulting in 68 respondents selected through purposive sampling based on their active involvement in sustainable education programmes. The research instrument was a questionnaire with a five-point Likert scale, while data analysis was performed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method using SmartPLS 4.0. The results showed that continuing education positively affected the effectiveness of environmental education management. Sustainable education has been proven to strengthen the capacity of individuals and institutions to manage environmental education in a consistent, focused, and sustainable manner. These findings confirm that the success of environmental education management depends not only on policies or curricula but also on the quality of the implementation of continuing education carried out systematically. The implications of this research provide a theoretical and practical basis for developing continuing education strategies in supporting environmental education management in various contexts.